Demography of the over-exploited Mediterranean red coral (Corrallium rubrum L. 1758) - Santangelo, G; Maggi, E.; Bramanti, L.; Bongiorni, L. (Scientia Marina, 2004)
The precious octocoral, Corallium rubrum, endemic to the Mediterranean, has long been overexploited. A demographic approach to the conservation and management of this species would therefore be highly valuable. To this end, a coastal population of red coral was studied in detail. The population represents a true "genetic unit", as it is mainly "self-seeding". It is moreover gonocoric, and the sex ratio is significantly biased toward females. For this study, 4408 colonies, collected from 28, 300-cm2 samples, were divided into 10 size (age) classes. Recruits represent about half the population. The frequency of colonies in each class decreases exponentially with colony size. On these bases, an "ad hoc" life history table has been updated to include the mortality and reproduction coefficients actually measured in the population. The major reproductive output is due to the first 3 reproductive classes (79%), while larger colonies, although having higher reproductive coefficients, are sparse and only account for a small portion of the population overall reproductive output. The ratio of larval survival to adult density found indicates that some density-dependent limitation of population growth is likely at play in the population under study. Such results will be important for understanding dynamics of red coral disturbed or exploited populations.